CORPORATE GOVERNANCE AND PROFITABILITY ON THE TIMELINESS OF FINANCIAL REPORTING: AN EMPIRICAL STUDY OF THE MINING SECTOR - Dwi Wahyuni, Putri (Dinasti Publisher, 2020)
The research objective to be achieved is to provide understanding and knowledge to the public, especially investors and creditors about the role of corporate governance (independent commissioners, the audit committee and institutional ownership) and return on assets (ROA) on the timeliness of financial reporting and can use as a reference for further researchers and stakeholders in making relevant and reliable decisions. The Population in this study is a listed mining sector issuer on the Indonesia Stock Exchange conducted for 3 years of observation in 2016 - 2018. Data collection techniques using a purposive sampling method. Analysis of the data used is logistic regression The results showed that only return on assets had a positive and significant effect on the timeliness of financial reporting. While the independent commissioner variable, the size of the audit committee and institutional ownership have an influence but are not significant